PENGARUH CELEBRITY ENDORSERS, PROMOSI PENJUALAN DAN KUALITAS INFORMASI TERHADAP KEPUTUSAN PEMBELIAN SHOPEEFOOD: STUDI PADA MAHASISWA PRODI MANAJEMEN UNIVERSITAS MUHAMMADIYAH GRESIK TAHUN 2018-2020 - Laily Hanifah; Moh. Agung Surianto (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Digitalization has led to many very rapid developments, especially in the field of technology. The development of information and communication technology has had an impact on changes in various fields, such as the economy, society, politics and culture, and has had an impact on lifestyle changes, including consumption patterns and the way people sell and shop. So a lot e-commerce has sprung up with attractive and safe shopping technology systems. E-commerce in Indonesia is currently growing rapidly by taking all market share from providing online selling platforms to ordering online food delivery. This change in the business environment has been taken advantage of by several technology-based companies, one of which is Gojek, Grab, and its new competitor, Shopeefood. Shopee is one of the largest e-commerce or online shopping sites in Indonesia. Shopee in April 2020 released its new delivery-food business called Shopeefood. This observation uses a quantitative technique with a questionnaire based on the calculation of the Likert scale. Validity and reliability tests have been used to decide whether the allocated questionnaire turns out to be valid or not. Hypothesis testing is carried out using multiple regression examinations, simultaneous trials (F-test), and testing and determining the correlation coefficient. From the results of the assessment carried out, it is recognized that the quality of information does not have an impact on purchasing decisions, while celebrity endorsers and sales promotions have an impact on purchasing decisions through Shopeefood.